Seasonal variation, fractional isolation and nanoencapsulation of antioxidant compounds of Indian blackberry (Syzygium cumini) - Shaheen, Rabia; Hanif, Muhammad Asif; Nisar, Shafaq; Rashid, Umer; Sajid, Zubia; Shehzad, Muhammad Raffi; Winkler-Moser, Jill K.; Alsalme, Ali (MDPI AG, 2021)
Indian blackberry (Syzygium cumini L.) is an evergreen tree in the Myrtaceae family. It is used in traditional medicine due to its significant bioactivities and presence of polyphenols with antioxidant activities. The present study describes the effect of seasonal variations on Indian blackberry leaf essential oil yield and chemical composition, production of fractions from essential oil using high vacuum fractional distillation and slow cooling to low temperature (−50 °C) under vacuum, and bioactivities of the essential oil, fractions, and nanoparticles. The results show that Indian blackberry essential oil yield was higher in spring season as compared to winter season. Indian blackberry essential oil fractionation processes were effective in separating and concentrating compounds with desired bioactivities. The bioactivities shown by magnesium nanoparticles were comparatively higher than barium nanoparticles.